TO STUDY THE PREVALENCE OF MRSA AND ITS ANTIMICROBIAL SUSCEPTIBILITY PATTERN AMONG STAPHYLOCOCCUS AUREUS ISOLATED FROM VARIOUS CLINICAL SAMPLES - Dr. Raees Ahmed; Dr. Anita E.Chand; Dr. Nashra Afaq (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a common nosocomial infection that causes severe morbidity and mortality. MRSA (methicillin-resistant S. aureus) is now endemic in India. In India, the prevalence of Methicillin-Resistant Staphylococcus aureus (MRSA) ranges between 30 to 70%, resulting in high mortality, increased economic burden, and treatment failure in tertiary care facilities. Rapid and consistent MRSA detection is crucial for infection control and preventing unnecessary antibiotic use. Aim and Objective:This study aimed to find out the prevalence of MRSA and to assess antibiotic activity against methicillin-resistant Staphylococcus aureus in vitro. Material and Methods: This was a Cross-sectional observational study carried out in the Department of Microbiology at Government Medical College, Kota, Rajasthanfor a period of three years, starting from September 7, 2019, to September 6, 2022. A total of 384 Staphylococcus aureus isolated from different clinical samples were analyzed. MRSA isolates were screened and confirmed using standard methods recommended by the Clinical and Laboratory Standards Institute (CLSI). Methicillin resistance, in Staphylococcus aureus strains, was evaluated using cefoxitin. The Kirby-Bauer disc diffusion technique was used to assess the antibiotic susceptibility pattern of all MRSA strains. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method according to the CLSI guidelines 2019. Results:In the present study a total of 384 Staphylococcus aureus isolates were obtained from various clinical samples. The prevalence of MRSA was observed to be 48.1%. Among 384 S. aureus isolates, 70 (18.23%) belonged to (21-30) age group followed by 67 (17.45%) and least was observed in the age group 15 (3.91%) from (0-10) age group. The ratio of males was more compared to the females 195 (50.7%), 189 (49%) respectively in case of S.aureus and for MRSA Male was observed to be 98 (52%), female 87 (47.2%) respectively. The maximum number of isolates were observed forpus followed by urine and least for pleural fluid. It was also noted that Vancomycin was found to be the most sensitive with the sensitivity of 97.3%, followed by Linezolid 96.2% and then Teicoplanin 89.73 % was found to be the most effective drug of choice. Conclusion: The prevalence of MRSA varies according to geographical region, hospital type, examined population, and detection technique. Effective antimicrobial activity as well as cost effectiveness should be considered in drugs prescribed for MRSA infections. Given the clinical implications of MRSA infection and its rapid transmission potential, MRSA strains must be evaluated on a frequent basis.